2022
DOI: 10.1063/5.0103018
|View full text |Cite
|
Sign up to set email alerts
|

High performance near-infrared MoTe2/Ge heterojunction photodetector fabricated by direct growth of Ge flake on MoTe2 film substrate

Abstract: We demonstrated a feasible strategy to fabricate MoTe2/Ge heterojunction by direct growth of Ge flake on a MoTe2 film substrate with a two-step chemical vapor deposition method. A thin transition layer (∼4 nm) mainly composed of polycrystalline germanium at the MoTe2/Ge interface was verified during the Ge flake growth. The MoTe2/Ge heterojunction-based photodetector exhibits both the response speed with a rise/fall time of 7/4 μs and the photoresponsivity and detectivity with 4.87 A W−1 and 5.02 × 1011 Jones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The enlarged I-V curves of the photodetector at 50 mV is displayed in figure 5 It is evident that the I ph of this device gradually increases from 2.6 nA at 800 nm to 9.7 nA at 1100 nm. This trend is due to the bandgap of the thicker MoTe 2 film close to ∼0.98 eV [2,16,23], corresponding to the peak absorption wavelength of ∼1270 nm. Therefore, the photodetector tends to increase the absorption of NIR with a wavelength of 800-1100 nm.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…The enlarged I-V curves of the photodetector at 50 mV is displayed in figure 5 It is evident that the I ph of this device gradually increases from 2.6 nA at 800 nm to 9.7 nA at 1100 nm. This trend is due to the bandgap of the thicker MoTe 2 film close to ∼0.98 eV [2,16,23], corresponding to the peak absorption wavelength of ∼1270 nm. Therefore, the photodetector tends to increase the absorption of NIR with a wavelength of 800-1100 nm.…”
Section: Resultsmentioning
confidence: 90%
“…Near-infrared (NIR) photodetectors, as key building blocks of photonic integrated circuits, exhibit attractive potential applications in optical communications, biomedical imaging, spectroscopy, and gas sensing [1][2][3][4]. To fabricate high-performance NIR photodetectors, various narrow-bandgap semiconductor materials, such as Si, Ge, InP, InGaAs, and two-dimensional (2D) transition metal dichalcogenides (TMDCs) [5][6][7][8][9][10][11], have attracted increasing attention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, a number of 2DLMs, including graphene [15], glassy graphene [16], graphdiyne [17], chalcogenides [18][19][20][21][22][23][24][25], MXenes [26], nitrides [27], phosphides [28], metal phosphorus trichalcogenides [29], as well as related heterostructures [30][31][32][33][34][35][36][37][38][39][40], have been developed for photoelectric detection research, and these materials have manifested a variety of intriguing characteristics. For example, by exploiting low-symmetry SiP 2 nanoflake as the photosensitive channel, Wang et al [28] demonstrated a unique polarization-sensitive photodetector with a dichroic ratio of ~1.…”
Section: Introductionmentioning
confidence: 99%